Contemporary diagnosis and management of Fournier’s gangrene - Chennamsetty, Avinash (Ther Adv Urol, 2015)
Fournier’s gangrene, an obliterative endarteritis of the subcutaneous arteries resulting in gangrene of the overlying skin, is a rare but severe infective necrotizing fasciitis of the external genitalia. Mainly associated with men and those over the age of 50, Fournier’s gangrene has been shown to have a predilection for patients with diabetes as well as people who are long-term alcohol misusers. The nidus for the synergistic polymicrobial infection is usually located in the genitourinary tract, lower gastointestinal tract or skin. Early diagnosis remains imperative as rapid progression of the gangrene can lead to multiorgan failure and death. The diagnosis is often made clinically, although radiography can be helpful when the diagnosis or the extent of the disease is difficult to discern. The Laboratory Risk Indicator for Necrotizing Fasciitis score can be used to stratify patients into low, moderate or high risk and the Fournier’s Gangrene Severity Index (FGSI) can also be used to determine the severity and prognosis of Fournier’s gangrene. Mainstays of treatment include rapid and aggressive surgical debridement of necrotized tissue, hemodynamic support with urgent resuscitation with fluids, and broad-spectrum parental antibiotics. After initial radical debridement, open wounds are generally managed with sterile dressings and negative-pressure wound therapy. In cases of severe perineal involvement, colostomy has been used for fecal diversion or alternatively, the Flexi-Seal Fecal Management System can be utilized to prevent fecal contamination of the wound. After extensive debridement, many patients sustain significant defects of the skin and soft tissue, creating a need for reconstructive surgery for satisfactory functional and cosmetic results.